2009
DOI: 10.1108/03074350910973685
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ETF splits on returns, liquidity, and individual investors

Abstract: Purpose -The purpose of this paper is to extend the literature on the effects of stock splits from mutual funds splits and the QQQ split to 20 exchange traded funds (ETFs) that span a wide variety of indexes. The split sample is compared to a non-split control sample with similar characteristics between 2000 and 2006. The objectives of this study are to investigate whether the results are different between the split sample and the control sample; and whether these results are similar to other investment vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(23 reference statements)
0
10
0
1
Order By: Relevance
“…On the other hand, other researchers (Chern et al 2008;Guo et al 2008;Yu and Webb 2009) found that stock splits reduce bid-ask spreads, and increase the number of small traders who are attracted to the lower price on Ex-date, indicating liquidity improvement. Mohanty and Moon (2007) also found a significant improvement in the average trading volume, comparing 12 months post splits announcement with that for prior to announcements.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…On the other hand, other researchers (Chern et al 2008;Guo et al 2008;Yu and Webb 2009) found that stock splits reduce bid-ask spreads, and increase the number of small traders who are attracted to the lower price on Ex-date, indicating liquidity improvement. Mohanty and Moon (2007) also found a significant improvement in the average trading volume, comparing 12 months post splits announcement with that for prior to announcements.…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…Since most ETFs actually hold the securities (baskets) as a way of tracking their return (as opposed to engaging in options/futures markets or performing partial replications of the index), any new ETF has the potential to significantly impact the underlying securities market in the process of obtaining these securities. Academics have examined the impact of ETF introductions on underlying stock's liquidity (Hegde and McDermott, 2004; Madura and Richie, 2007; Hamm, 2011; De Winne et al , 2011), volatility and turnover (Ben‐David et al , 2012), spot‐futures trading (Deville et al , 2012), and splits (Yu and Webb, 2009). Our study contributes to this literature by studying the impact of ETF introductions on stock's short interest levels.…”
Section: Related Literaturementioning
confidence: 99%
“…In general ETFs have become popular with institutional investors due to ease of use, instant diversification, low trading costs, easy access, and superior liquidity [1][2][3]. As fixed income ETFs have become more popular these traits are becoming more predominant in this market as well.…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to establish the relation between equity market uncertainty and participation in fixed income ETFs. Changes in volume and VIX are preferable to levels as the levels are non-stationary 2 . In addition to changes in the level of VIX, we also examine changes in risk aversion and uncertainty which are decomposed from VIX following Bekaert et al [15] and Bekaert and Hoerova [16].…”
Section: Introductionmentioning
confidence: 99%